Being an Involved Father: What Does It Mean? - Garret D. Evans; Kate Fogarty (EDIS)
It seems that more and more folks are sharing the message that fathers should be more involved in caring for their children. You may hear this message on TV, on the radio, where you worship, at school, at meetings, at work, and, especially, at home. Father involvement is defined as, men's “positive, wide-ranging, and active participation in their children's lives” (Marsiglio et al., 2000, p. 276). This document is FCS2141, one of a series of the Family, Youth, and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: December 1999. Revised: July 2005.